Outpatient Information System at X Bogor Web-Based Clinic - Abdul Robi Padri (Politeknik Siber Cerdika Internasional, 2021)
The clinic as one of the public service agencies requires the awareness of an accurate and reliable information system, and is adequate to improve its services to patients and other related environments. With such a wide scope of service, of course there are many complex problems that occur in the service process in the clinic. The number of variables in the clinic also determines the speed of information flow required by users and the PHP clinic environment can also be integrated with HTML, JavaScript, Jquery, and Ajax. However, in general PHP is more widely used in conjunction with HTML-type files. By using PHP we can create a dynamic powerful website with the accompanied database management. In addition, the use of PHP, which can mostly be used on many platforms, is one of the reasons why you have to master PHP to become a reliable web development.